A STUDY OF DECISION TREE ALGORITHMS FOR CONTINUOUS ATTRIBUTES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
Nowadays a lot of different algorithms for decision trees construction exist. With the help o f these algorithms one can make classification o f both discrete and continuous data. The aim o f this paper is to explore decision tree algorithms for continuous attributes. There are investigated CART (Breiman et al, 1984) and C4.5 (Quinlan, 1992) in this paper. The comparison of these methods was done in the process of exploration. As a result of the usage o f both algorithms, the conclusions about CART and C4.5 utilization advantages were drawn.